Active Labour Market Policies and Macroeconomic Variables on Employment, Informal Employment and Income Effects: The case of Turkey - Basbuga, Halit; Kitapci, Hakan; Oguz, Enes Cengiz; Elkoca, Yusuf (International Journal of Economics and Financial Issues, 2022)
In this empirical research, the effects of macroeconomic variables and the incentive policies implemented in Turkey on the employment, informal employment and income have been investigated in Turkey. Electricity consumption (Economic Growth), the USD/TL exchange rate and inflation variables were used as the macroeconomic variables. The employment incentives that are implemented by the Laws Number 5510, 25510/16322, 26322, 6111, 14857 and 05746/15746 among the employment incentive policies implemented in Turkey were used as variables. The first lagged values of employment incentives from the Laws No. 5510, 26322 and 6111 significantly affected informal employment. The first lagged values of the variables of economic growth as the macroeconomic variable and Law No. 5510 have a positive effect on reducing informal employment. As a macro-economic variable, USD/TL exchange rate has a negative and relatively high efficiency.